A PROSPECTIVE STUDY ON CORRELATION OF HYPERCHLOREMIA WITH MORTALITY IN INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL. - Nezammudin, Md; Arun, Nidhi; Radheshyam; Kumar, Sanjeev (Student's Journal of Health Research Africa, 2023)
Introduction: Serum chloride (Cl−) is a crucial extracellular anion with significant medical importance. Hypochloremia has been identified as an autonomous predictor of mortality based on emerging evidence gathered from patients diagnosed with kidney or heart disease. However, an overabundance of chloride ions (Cl−) can lead to fatality in critically unwell individuals. The objective of the research was to assess the frequency of hyperchloremia among deceased patients, with the aim of modifying our clinical approach by replacing chloride-rich solutions with solutions containing appropriate chloride levels (such as lactated ringer or plasmalyte) to prevent this iatrogenic complication. This may have potential benefits for our patients in the future. Methods: This prospective study was conducted at the Indira Gandhi Institute of Medical Sciences, Patna over a period of one year, from October 2021 to November 2022. This study comprised a sample size of 100 patients who were classified into two distinct groups based on their medical diagnosis. Results: The study's findings indicate that among the Non sepsis Groups, patients aged <=40 years accounted for 16.0% of the sample, while patients aged 41-60 years accounted for 30.0%, patients aged 61-80 years accounted for 46.0%, and patients aged >80 years accounted for 8.0%. The findings of the study indicate that there was no statistically significant variance in the average Chloride Value across the various time intervals. Conclusion: The administration of chloride-rich solutions in ICU patients necessitating large volume fluid resuscitation should be approached with caution to mitigate the effects of hyperchloremia.